2022
DOI: 10.1155/2022/4380901
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Mathematical Methods in Medicine Glioma Brain Tumor Detection and Classification Using Convolutional Neural Network

Abstract: The classification of the brain tumor image is playing a vital role in the medical image domain, and it directly assists the clinicians to understand the severity and to take an appropriate solution. The magnetic resonance imaging tool is used to analyze the brain tissues and to examine the different portion of brain circumstance. We propose the convolutional neural network database learning along with neighboring network limitation (CDBLNL) technique for brain tumor image classification in medical image proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This innovative approach yields results that are both objectively and subjectively compelling in terms of categorization. Validated using two datasets, BRATS and REMBRANDT, the proposed brain MRI classification algorithm surpasses the performance of existing methods 26 . Employing a multi-stage approach, the proposed method commences with preprocessing MRI images to eliminate noise and artifacts using an adaptive filter.…”
Section: Related Workmentioning
confidence: 92%
“…This innovative approach yields results that are both objectively and subjectively compelling in terms of categorization. Validated using two datasets, BRATS and REMBRANDT, the proposed brain MRI classification algorithm surpasses the performance of existing methods 26 . Employing a multi-stage approach, the proposed method commences with preprocessing MRI images to eliminate noise and artifacts using an adaptive filter.…”
Section: Related Workmentioning
confidence: 92%
“…In the presented approach, a stretched convolutional neural network is combined with pre- and post-processing methods to enlarge the receptive field. As a result, big distance pixels in source images will help enrich the image features of the learned model, which effectively denoises the images [ 16 ]. The author proposes a lightweight, effective neural network-based raw image denoiser that works well on popular mobile devices and yields great-quality noise-removal results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The various methods currently employed to identify brain tumors are covered in this section. Saravanan et al [ 13 ] proposed that brain tumors could be automatically segmented and identified using a deep learning-based image analysis technique. This proposed a technology that is accurate and computationally effective for segmenting brain tumors.…”
Section: Related Workmentioning
confidence: 99%